A Chick Embryo With a yet Unclassified Type of Cephalothoracopagus Malformation and a Hypothesis for Explaining its Genesis. (13th September 2012) - Maurer, B.; Geyer, S. H.; Weninger, W. J.
Summary Cephalothoracopagus embryos are conjoined twins, who share parts of their heads, necks and bodies. Our study aims at presenting a detailed morphological analysis of a cephalothoracopagus chick embryo of developmental stage 31. Because none of the existing theories can explain the genesis of the phenotype of this embryo, we also suggest a hypothesis, which explains it. Beside the cephalothoracopagus embryo, we investigated five control embryos. With the aid of the high‐resolution episcopic microscopy (HREM) technique, we created digital volume data and three‐dimensional (3D) computer models of the organs and arteries of the embryos. We used the 3D models for topological analysis and for measuring the diameters of the great intrathoracic arteries. The malformed embryo showed two body backs, each containing a notochord, spinal cord and dorsal aorta. The body backs continued into separated lower bodies. The embryo had a single, four‐chambered heart, single respiratory tract and single upper alimentary tract. The topology of the pharyngeal arch arteries was normal, and the diameters of these arteries were similar to that of the control embryos. We classified the embryo we investigated as a yet unknown malformation and suggest a hypothesis explaining its genesis.